Model Moderasi Beragama Pada Masyarakat Tolonggeru Bima Dalam Bingkai Pendidikan Islam - Salam, Abd (LP2M Universitas Islam Ahmad Dahlan, 2024)
This study aims to analyze the model of religious moderation within the community of Tolonggeru Hamlet, Bima Regency, in the context of Islamic education. The research employs both quantitative and qualitative approaches, using bibliometric analysis methods with tools such as Publish or Perish and VosViewer to analyze literature trends related to religious moderation in Islamic education. Additionally, the qualitative approach is applied through field observations, in-depth interviews with religious and community leaders, and document analysis to explore the practice of religious moderation in the local community. The results of the study indicate that religious moderation in Tolonggeru Hamlet is realized through a combination of Islamic education principles that prioritize tolerance and respect for diversity and local values that promote harmonious social life, such as mutual cooperation (gotong royong) and interfaith respect. Both formal and non-formal Islamic education play a significant role in shaping a moderate understanding and encouraging interfaith dialogue. The role of religious and community leaders in facilitating open communication and teaching moderation values serves as a key factor in maintaining harmony within a pluralistic society.